Statistical quality control study on Company B+ - LaMadrid, Ma. Inez; Poblete, Natalie Ian.; Villanueva, Racquel (Diliman, Quezon City College of Engineering, 2003)
Co. B+ is the largest manufacturer, exporter and distributor of automotive, industrial, valve-regulated, and motorcycle battery products in the Philippines. Despite being in the business for almost a century and having renewed ISO accreditations through the years, it does not exempt itself from experiencing quality ptoblems. A quality control study is done on Co. B+ to address the problems relating to quality. Three main problems were identified using the Pareto Analysis and the Ishikawa Method. The major causes of rejection addressed by the group are high free metallic lead (FML) content in BALOX, high moisture content in Pasting and overweight grids in Casting. The high free metallic lead percentage is brought about by high pot temperature setting and low panel blade speed. Conveyor speed and oven temperature are variables which affect moisture content. In the overweight grid problem, the causes are high temperature setting, irregular application of mold, bad mold coating formulation and poor mold condition. As supplement study, a minor attribute problem, which is the presence of vacuum in Casting, was also discussed. After doing Statistical Process Control (SCP) on the 4 quality problems, the group found out that except for the attribute problem (i,e, presence vacuums), the processes for the other quality problems were out of control. Both the X-bar charts for high moisture content and overweight grids exhibit non-randomness when subjected to SHewhart Control Chart Tests for Assignable Causes. From these tests, the out-of-control condition was attributed to the gradual deterioration of equipment. The Process Capability Analysis was done next which showed relatively low capability indices for the processes. All of the process capability indices are all less than 1.33, meaning that the three processes are all incapable. The values for Cp for BALOX, Pasting and Casting are 0.6175, 0.6809 and 0.4547, respectively. After ehich, the group conducted acceptance sampling and quality cost analyses.
Generally, the major causes of the three problems are machine operator related. The group cited specific recommended solutions for each problem. For the high %FML problem, the group suggests that the company make use of water as the cooling medium instead of air since it is a more effective medium. To remedy the warping problem which primarily causes the low panel blade speed, it is recommended to form a Quality Team that will aim to research on the type of metal for the reactor pot that would have a low coefficient of thermal expansion. For the moisture content problem, the group recommends the use of Single Factor Analysis of Variance (ANOVA) and Residual Analysis to find the range of temperature that would have the lowest variability. In this way, the company can minimize nonconformities due to temperature setting. Also, it is imperative that the company change the conveyor belt every 4 days, which is actually its useful life based on 6 months of data regarding the belts replacement frequency. Finally, for the overweight grid problem, Single Factor ANOVA and Residual Analyis are again performed to find the optimal temperature range. As part of the general recommended solutions, the group suggests the implementation of control charts and the Out-of-Control Action Plan (OCAP) for quick monitoring and detection. OCAP is a flow diagram of procedures to follow upon the occurrence of out of control points in the control charts. A revision of specification limits is also recommended and the suggested values are given. The group feels that the wide specification limits contribute to the low capability indices. For the areas of further study, the group mentioned a potential SPC study for the Curing process since it recently underwent major innovations. A study would be helpful in determining whether the changes improve the capability of the process. To find a more accurate range of temperature levels for both Pasting and Casting, a Design of Experiment study could also be useful for the company.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Electronics industry; Quality control